Acute effects of blood flow restriction training at various arterial occlusion pressures on muscle activation, blood lactate responses, and RPE in healthy adult males - Zhu, Hao; Tan, Zhaowen; Zhang, Nianyun; Li, Yang; Qi, Hu (Frontiers in Physiology, 2025)
BackgroundBlood flow restriction training (BFRT) can induce significant muscle activation and metabolic stress at low loads. However, the acute physiological and perceptual responses to different arterial occlusion pressures (AOPs) remain unclear. This study aimed to examine the effects of varying AOP levels on muscle activation, blood lactate concentration, and ratings of perceived exertion (RPE) during low-load resistance exercise in healthy young males.MethodsSixteen healthy males (20.4 ± 1.5 years) participated in a single-group, repeated-measures study. Each performed barbell back squats (20% 1RM) under four AOP conditions: 0%, 60%, 70%, and 80% AOP. Muscle activation (%MVC), blood lactate concentrations, and RPE were assessed. One-way and two-way repeated-measures ANOVAs were used to analyze the outcomes across pressure and time conditions.ResultsMuscle activation increased significantly at 70% and 80% AOP compared to 0% and 60% (e.g., semitendinosus: F (3, 45) = 15.79, p < 0.001, ηp2 = 0.51, 95% CI [0.14, 0.40]), with no difference between 70% and 80% AOP. Blood lactate concentrations increased significantly post-exercise under 70% and 80% AOP (F (3, 45) = 4.82, p = 0.005, ηp2 = 0.24, 95% CI [0.03, 0.22]), although the main effect of pressure was not significant across time points (F (3, 45) = 1.63, p = 0.192, ηp2 = 0.08, 95% CI [0.01, 0.13]). RPE increased progressively with pressure (F (1.80, 26.94) = 25.34, p < 0.001, ηp2 = 0.63, 95% CI [0.28, 0.66]), and was highest at 80% AOP.Conclusion70%–80% AOPs elicited greater acute neuromuscular and metabolic responses compared to lower pressures, with 70% AOP achieving similar physiological outcomes as 80% but with lower perceived exertion. These findings provide practical guidance for selecting relative occlusion pressures during BFRT. Further studies are warranted to explore long-term training adaptations at these pressures.